N-subsituted homopiperazine barbiturates as gelatinase inhibitors - RADOMSKI, MAREK; WANG, JUN; MEDINA MARTIN, CARLOS; GILMER, JOHN (My University, 2011)
Matrix metalloproteinases are implicated in a wide range of pathophysiological processes and potent selective inhibitors for these enzymes continue to be eagerly sought. 5,5-Disubstituted barbiturates hold promise as inhibitor types being stable in vivo and relatively selective for the gelatinases (MMP-2 and MMP-9). In this paper we describe the synthesis of 5-piperazine and -homopiperazine substituted barbiturates. The activity of these compounds as gelatinase inhibitors was evaluated using supernatants from 12-O-tetradecanoylphorbol-13-acetate (PMA) - stimulated HT-1080 cells as well as using recombinant human MMPs. N-acyl homopiperazine compounds were found to be potent inhibitors of the gelatinases (range in nM) and generally more potent than the corresponding piperazine analogs. The panel of N-acyl homopiperazines was enlarged in order to exploit differences between the gelatinases at the S2? site in order to design MMP-2- or MMP-9-selective inhibitors. Compounds in this group exhibited single digit nano-molar potency and some selectivity between the two enzymes. Representative potent compounds were effective inhibitors of cancer cell migration.
PUBLISHED
Keywords: Biochemistry; Matrix metalloproteinases